2010
DOI: 10.1002/zoo.20301
|View full text |Cite
|
Sign up to set email alerts
|

Habituation to environmental enrichment in captive sloth bears—effect on stereotypies

Abstract: The benefits to captive animals of environmental enrichment (EE) are widely recognized. Few studies have, however, studied how to maximise the effect of EE. One issue with EE programs seems to be habituation to the enrichment device. To study the effect of habituation to EE, 14 captive sloth bears (Melursus ursinus) were subjected to two different EE treatments. Treatment one presented EE (logs with honey containing holes) for five consecutive days, whereas treatment two presented EE on intermittent days for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 24 publications
2
36
0
3
Order By: Relevance
“…Prior research has tied pacing to various direct causes such as lack of novel enrichment, anticipation of husbandry events, or enclosure limitations (Anderson et al, 2010;Jenny and Schmid, 2002;Mountaudouin and Pape, 2004;Papadouka and Matthews, 1995;Ross, 2006;Watters, 2014). Possibly because of the great variety of situations and stimuli that elicit pacing, research differs in conclusions as to the abnormality of the behavior, or whether or not it represents some sort of variation of a species-typical behavior seen in the wild, such as roaming behavior observed in wild polar bears (Amstrup et al, 2000;Ferguson et al, 1999).…”
Section: Introductionmentioning
confidence: 95%
“…Prior research has tied pacing to various direct causes such as lack of novel enrichment, anticipation of husbandry events, or enclosure limitations (Anderson et al, 2010;Jenny and Schmid, 2002;Mountaudouin and Pape, 2004;Papadouka and Matthews, 1995;Ross, 2006;Watters, 2014). Possibly because of the great variety of situations and stimuli that elicit pacing, research differs in conclusions as to the abnormality of the behavior, or whether or not it represents some sort of variation of a species-typical behavior seen in the wild, such as roaming behavior observed in wild polar bears (Amstrup et al, 2000;Ferguson et al, 1999).…”
Section: Introductionmentioning
confidence: 95%
“…Habituation to enrichment items has been observed in many captive animals, such as pigs (Sus spp. ), Western lowland gorillas (Gorilla gorilla gorilla), sloth bears (Melursus ursinus), and American black (Ursus americanus) and brown (Ursus arctos) bears [Anderson et al, 2010;Carlstead et al, 1991;Robbins and Margulis, 2014;Trickett et al, 2009]. Since the four elephants in the present study quickly habituated to the two auditory stimuli provided, it is plausible that captive elephants, in general, will habituate to auditory enrichment.…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, chili powder catapults [Le Bel et al, 2010] could be used with the sound of bee buzzing to add a form of positive punishment that is absent with just the sound playback. Researchers have also suggested that habituation could be delayed if longer time gaps were inserted in between presentations of the same stimulus [Anderson et al, 2010;Murphy et al, 2003;Tarou and Bashaw, 2007].…”
Section: Discussionmentioning
confidence: 99%
“…In a study on Ailuropoda melanoleuca, the authors classified 11 different types of stereotypies, mainly motor and oral (Lindburg et al, 2001). And finally, in a study on Melursus ursinus, the authors studied the effect of environmental enrichment on stereotypies in order to improve bear welfare (Anderson et al, 2010).…”
Section: Soriano Vinyoles Matémentioning
confidence: 99%